Solar cell, grid line structure thereof, grid line preparation method, and laminated cell and photovoltaic module

CN122180195BActive Publication Date: 2026-10-30HUAIAN JIETAI NEW ENERGY TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610648236.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-12
Publication Date
2026-10-30
Estimated Expiration
2046-05-12

AI Technical Summary

Technical Problem

尽管非银丝网印刷浆料(如铜、铝、镍、锡、锌基浆料)已在多个行业广泛应用,但在硅太阳能电池中的应用仍存在局限且面临挑战,尤其是在需要形成金属与硅直接接触界面的场景中

Benefits of technology

(1)本发明的栅线结构包括第一金属层和第二金属层,其中第一金属层作为种子层,通过对第一金属层的表面形貌和表面粗糙度进行优化设计,使得第一金属层的比表面积增大,不仅有利于上层金属与下层金属之间形成更大接触界面,有效降低两种金属层之间的界面电阻,从而降低第二金属层对银含的依赖,进而降低栅线浆料中的总体银含以及电池制造成本;同时,还能够降低第二金属层对第一金属层接触面积的依赖,从而有效降低工艺难度,使得第一金属层和第二金属层之间部分重叠或交叉即可。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122180195B_ABST
    Figure CN122180195B_ABST
Patent Text Reader

Abstract

The application discloses a solar cell, a grid line structure of the solar cell, a grid line preparation method, a laminated cell and a photovoltaic module, and belongs to the technical field of photovoltaics. The grid line structure comprises a first metal layer and a second metal layer, the first metal layer is used as a seed layer and adopts a first paste; along the length extension direction of the grid line, the surface profile of the first metal layer comprises alternating convex regions and concave regions, wherein the convex regions and the concave regions have a height difference; the second metal layer adopts a second paste, and metal particles with different particle sizes are alternately stacked in the second metal layer; the silver content of the first paste is greater than the silver content of the second paste, and the first metal layer and the second metal layer at least partially overlap or intersect. The application optimizes the surface morphology and the surface level roughness distribution of the first metal layer, so that the silver content in the paste and the cell manufacturing cost can be effectively reduced, and the interface resistance between the two metal layers can be reduced, thereby preventing the line resistance of the cell from increasing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photovoltaic technology, and more specifically, relates to a solar cell, its grid structure, grid fabrication method, as well as tandem cells and photovoltaic modules. Background Technology

[0002] Photovoltaic power generation is one of the main ways to utilize solar energy. Due to its cleanliness, safety, convenience, and high efficiency, solar photovoltaic power generation has become a new industry of widespread attention and key development in countries around the world. Therefore, in-depth research and utilization of solar energy resources are of great significance for alleviating the resource crisis and improving the ecological environment.

[0003] Solar cells typically use conductive silver paste as the main and secondary grid metal electrodes to collect the photocurrent generated by the cell substrate. The secondary grid electrodes are connected to the main grid formed by the silver paste, and the current from the secondary grid is collected and output through the main grid. The conductive silver paste for solar cells is mainly a mechanical mixture of silver powder (conductive phase or conductive filler), glass powder (binder phase), organic carrier, and other additives (auxiliaries) in a certain proportion.

[0004] Currently, conductive silver paste for solar cells in existing technologies typically uses high-temperature pastes with high silver content (usually greater than 90%) (sintering at peak temperatures exceeding 650°C) to achieve silver-silicon alloy contact with the silicon wafer. However, this method consumes a large amount of silver and has a high price, making it difficult to reduce the manufacturing cost of the cells. Furthermore, the organic matter in the paste rapidly volatilizes during high-temperature heating, forming a large number of voids. The formation of voids reduces the effective cross-sectional area, thus adversely affecting the line resistance.

[0005] To effectively reduce battery manufacturing costs, many researchers have begun exploring the use of cheaper and more abundant low-silver or non-silver pastes to replace silver, thereby reducing the photovoltaic industry's dependence on silver. Although non-silver screen printing pastes (such as copper, aluminum, nickel, tin, and zinc-based pastes) are widely used in many industries, their application in silicon solar cells remains limited and challenging, especially in scenarios where a direct metal-silicon interface needs to be formed.

[0006] Therefore, it is of great significance to explore how to use and replace silver paste or non-silver paste to reduce paste costs and ensure the performance of photovoltaic cells, especially the interface performance. Summary of the Invention

[0007] The main objective of this invention is to provide a grid structure for a solar cell, comprising a first metal layer and a second metal layer formed by overprinting. By optimizing the surface roughness distribution of the first metal layer, the silver content of the second metal layer can be effectively reduced, thereby reducing the overall silver content in the paste and the cost of cell production. Furthermore, it can effectively ensure good contact between the two metal layers, reducing interface resistance. Simultaneously, the grid structure of this invention can effectively reduce the difficulty of cell production processes, as the first and second metal layers only need to partially overlap or intersect. The present invention also provides a method for preparing the above-mentioned grid structure, which obtains two metal layers by sequentially overprinting two metal layers through a step-by-step printing process, thereby reducing the cost and amount of silver used and the difficulty of the process, and achieving the goal of reducing the line resistance of the battery cell. The present invention also provides a solar cell comprising the above-described grid structure; The present invention also provides a stacked battery comprising the above-described grid structure or solar cell; The present invention also provides a photovoltaic module comprising the above-described grid structure, or solar cell, or tandem cell.

[0008] To achieve the above objectives, the technical solution provided by the present invention is as follows: The first aspect of the present invention provides a grid structure for a solar cell, comprising a first metal layer and a second metal layer, wherein: The first metal layer serves as a seed layer, and it is made from a first slurry; Along the length extension direction of the gate line, the surface profile of the first metal layer includes alternating raised and recessed regions, wherein there is a height difference between the raised and recessed regions; The second metal layer is made of a second slurry, and metal particles of different sizes are stacked alternately within the second metal layer; The silver content of the first slurry is greater than that of the second slurry, and the first metal layer and the second metal layer at least partially overlap or intersect.

[0009] According to any of the embodiments described in the first aspect of the present invention, the silver content of the first slurry is 70wt% to 92wt%, and / or the silver content of the second slurry is less than 30wt%.

[0010] Furthermore, the glass phase in the first slurry accounts for 0.5% to 5% of the total mass; And / or the volume resistivity of the second slurry after sintering is 3~9 μΩ·cm.

[0011] According to any of the embodiments described in the first aspect of the present invention, the horizontal distance L1 between the highest points of adjacent protruding regions is 20 to 100 micrometers; The height difference h1 between the highest point of adjacent raised and recessed areas is 0.01 to 5 micrometers.

[0012] According to any of the embodiments described in the first aspect of the present invention, the raised region and / or recessed region have sections with gentle height undulations.

[0013] Furthermore, the gently undulating section includes small bumps and depressions that are alternately distributed along the length of the grid line (i.e., there are high and low undulations), where the small bumps and depressions are intended to emphasize that the degree of high and low undulations is small.

[0014] Furthermore, the height range h2 of the gently undulating section is 0.01~3 micrometers.

[0015] Furthermore, the horizontal distance L2 between the highest points of adjacent small protrusions in the gently undulating section is 0.01~10 micrometers.

[0016] According to any embodiment of the first aspect of the present invention, the area of ​​the second metal layer covering the first metal layer is 20% to 100% of the total area of ​​the first metal layer.

[0017] According to any of the embodiments described in the first aspect of the present invention, the printing width of the first metal layer is 5 to 50 micrometers and the printing height is 0.5 to 3 micrometers; the printing width after superimposing the second metal layer is 10 to 100 micrometers and the printing height is 1 to 30 micrometers.

[0018] According to any of the embodiments described in the first aspect of the present invention, the first metal layer and the second metal layer are formed by screen printing.

[0019] According to any of the embodiments described in the first aspect of the present invention, irregular pores (also referred to as voids) are formed in the first metal layer.

[0020] Furthermore, the length and width of the pores (also referred to as voids) are both between 0.1 and 10 micrometers.

[0021] According to any embodiment of the first aspect of the present invention, the metal particles with different particle sizes in the second metal layer include large metal particles with a particle size of 0.2 to 10 micrometers and nano metal particles with a particle size of 10 to 1000 nanometers.

[0022] Furthermore, the large metal particles are made of pure copper, nickel, silver-coated copper, silver-coated nickel, or any combination thereof; the nano metals are made of nano silver powder, nano nickel powder, nano copper powder, or any combination thereof.

[0023] Furthermore, the surface of the first metal layer has pores (also called voids), and at least a portion of the pores (also called voids) on the surface of the first metal layer are filled with nano-metals.

[0024] According to any embodiment of the first aspect of the invention, the line resistance of the gate wire is 1~5 Ω / cm, and the contact resistivity is 1~4 mΩ / cm. 2 .

[0025] A second aspect of the present invention provides a method for fabricating a grid structure for a solar cell, comprising: The first metal layer is formed on the surface of the semiconductor substrate of the solar cell by screen printing technology; A second metal layer is formed on the surface of a semiconductor substrate of a solar cell by screen printing, which at least partially overlaps or intersects with the first metal layer.

[0026] A third aspect of the present invention provides a solar cell comprising a semiconductor substrate, wherein the surface of the semiconductor substrate is provided with the grid line structure described in the first aspect of the present invention.

[0027] Furthermore, the gate line structure is located on the front or back side of the semiconductor substrate; and / or the gate line structure is a main gate or a sub-gate.

[0028] The fourth aspect of the present invention provides a stacked battery, comprising a top battery, an intermediate connecting layer and a bottom battery stacked sequentially, wherein the bottom battery is provided with the grid structure described in the first aspect of the present invention, or adopts the solar cell described in the third aspect of the present invention.

[0029] The fifth aspect of the present invention provides a photovoltaic module, including the grid structure described in the first aspect of the present invention, or including the solar cell described in the third aspect of the present invention, or including the tandem cell described in the fourth aspect of the present invention.

[0030] Compared with the prior art, the technical solution provided by this invention can achieve the following beneficial effects: (1) The grid structure of the present invention includes a first metal layer and a second metal layer, wherein the first metal layer serves as a seed layer. By optimizing the surface morphology and surface roughness of the first metal layer, the specific surface area of ​​the first metal layer is increased. This not only facilitates the formation of a larger contact interface between the upper and lower metal layers, effectively reducing the interface resistance between the two metal layers, but also reduces the dependence of the second metal layer on silver content, thereby reducing the overall silver content in the grid paste and the battery manufacturing cost. At the same time, it can also reduce the dependence of the second metal layer on the contact area of ​​the first metal layer, thereby effectively reducing the process difficulty, so that the first metal layer and the second metal layer can partially overlap or cross each other.

[0031] (2) The present invention further optimizes the horizontal spacing between the highest points of adjacent raised areas and the height difference between the highest points of adjacent raised areas and recessed areas, thereby helping to further ensure the overprinting effect between the upper and lower metal layers and improve conductivity and adhesion.

[0032] (3) The second slurry of the present invention contains large metal particles with a particle size of 0.2 to 10 micrometers and nano metal particles with a particle size of 10 to 1000 nanometers. By utilizing the stacking and filling effect between particles of different sizes during the printing process, the number of pores / voids in the second metal layer can be effectively reduced, and void-free filling can be basically achieved, which greatly improves the density of the second metal layer and prevents the pores / voids from affecting the line resistance of the battery cell. At the same time, the nanoparticles can also fill the pores / voids on the surface of the first metal layer, thereby increasing the contact area between the two slurries, reducing the interfacial resistance between the two materials, which is conducive to further reducing the line resistance and is more conducive to electron transport.

[0033] (4) In the present invention, under the superimposed second metal layer system: the printing width of the first metal layer is 5~50 micrometers and the printing height is 0.5~3.5 micrometers; the overall printing width of the gate line after superimposing the second metal layer is 10~100 micrometers and the printing height is 1~30 micrometers. The seed layer paste with low wet weight can form a good ohmic contact with the silicon wafer and the contact resistance is not higher than the basic state; while by overprinting the second metal layer, the line resistance can be not higher than the basic state.

[0034] (5) In this invention, the glass phase in the first slurry accounts for 0.5% to 5% of the mass. By adjusting the glass corrosivity of the seed layer, the mold opening rate of the seed layer slurry corroding silicon nitride and alumina is not higher than that of the basic state, thus further ensuring a good contact resistance level.

[0035] (6) The grid structure of the present invention can be applied to the front grid line of the battery cell or the back grid line of the battery cell. It can also be used as the main grid of the battery cell or as the sub-grid of the battery cell. Attached Figure Description

[0036] Figure 1 This is a schematic diagram of the gate wire structure according to one embodiment of this application; Figure 2 This is a schematic diagram of the surface contour of the first metal layer in one embodiment of this application; Figure 3 This is a schematic diagram of the surface contour of the first metal layer according to another embodiment of this application; Figure 4 These are illustrations showing the effects of different overprinting and intersecting patterns of the first and second metal layers in this application. Figure 5This is a schematic diagram showing the distribution of the first and second metal layers under one of the following conditions; Figure 6 This is a cross-sectional scan diagram of the fine grid on the back of the battery cell obtained in Example 1; Figure 7 This is a cross-sectional scan diagram of the second metal layer in Example 1; Figure 8 This is a scanned image of one of the back-side fine grids in Example 1; Figure 9 for Figure 8 Schematic diagram of the height distribution of the fine grid along the length of the grid line on the middle and back sides; Figure 10 for Figure 8 Dimensional distribution of the cross-section (perpendicular to the length of the grid line) of the fine grid on the middle and back sides; Figure 11 for Figure 8 The fine grille on the middle and back sides (position different) Figure 10 Dimension distribution diagram of the cross section (perpendicular to the length direction of the grid line); Figure 12 This is a scanned image of another back-side fine grid in Example 1; Figure 13 for Figure 12 Schematic diagram of the height distribution of the fine grid along the length of the grid line on the middle and back sides; Figure 14 for Figure 12 Dimensional distribution of the cross-section (perpendicular to the length of the grid line) of the fine grid on the middle and back sides; Figure 15 for Figure 12 The fine grille on the middle and back sides (position different) Figure 14 Dimension distribution diagram of the cross section (perpendicular to the length direction of the grid line); Figure 16 This is a scanned image of another back-side fine grid in Example 1; Figure 17 for Figure 16 Schematic diagram of the height distribution of the fine grid along the length of the grid line on the middle and back sides; Figure 18 for Figure 16 Dimensional distribution of the cross-section (perpendicular to the length of the grid line) of the fine grid on the middle and back sides; Figure 19 for Figure 16 The fine grille on the middle and back sides (position different) Figure 18 Dimension distribution diagram of the cross section (perpendicular to the length direction of the grid line); In the figure: 1. First metal layer; 2. Second metal layer; 3. Pores; 4. Nanometal; 5. Large metal particles. Detailed Implementation

[0037] The present disclosure will now be described with reference to the accompanying drawings and specific embodiments. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the disclosure. In the following detailed description, numerous specific details are set forth to provide a thorough understanding of the embodiments of the present disclosure for ease of explanation. However, it will be apparent that one or more embodiments may be practiced without these specific details. Furthermore, descriptions of well-known structures and technologies are omitted in the following description to avoid unnecessarily obscuring the concepts of the present disclosure.

[0038] It should be noted that the terminology used herein is for the purpose of describing specific embodiments only and is not intended to limit this disclosure, and all terms used herein (including technical and scientific terms) have the meanings commonly understood by those skilled in the art, unless otherwise defined. It should be understood that the terms used herein should be interpreted in a manner consistent with the context of this specification and should not be interpreted in an idealized or overly rigid manner.

[0039] It should be understood that the terms “comprising”, “including”, etc., used herein indicate the presence of the said features, steps, operations and / or components, but do not exclude the presence or addition of one or more other features, steps, operations or components.

[0040] Furthermore, the terms "first," "second," etc., used in the specification, claims, and accompanying drawings of this application are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be interchanged where appropriate for the embodiments of this application described herein.

[0041] Currently, the grid lines of existing solar cells are usually printed using high-silver-content paste. On the one hand, the silver consumption is large, resulting in higher manufacturing costs for the cells. On the other hand, the organic matter in the paste volatilizes rapidly when heated to high temperatures, forming a large number of voids. The formation of voids reduces the effective cross-sectional area and has an adverse effect on the line resistance.

[0042] Based on the above, this application provides a grid line structure for a solar cell and optimizes the grid line structure as follows: Specifically, such as Figure 1 As shown, the grid line structure of this embodiment includes a first metal layer 1 and a second metal layer 2 that are overlaid or superimposed on each other. The first metal layer 1 serves as a seed layer and is made of a first paste with a high silver content, thereby forming a good ohmic contact with the semiconductor substrate of the battery cell.

[0043] Furthermore, the silver content of the first slurry is 70% to 92%; for example, the silver content can be 70%, 75%, 80%, 83%, 89%, or 92%, etc.

[0044] More preferably, the glass phase (various salts, oxides, etc. that participate in the reaction) in the first slurry accounts for 0.5% to 5% by mass. By adjusting the glass corrosivity of the seed layer, the mold opening rate of the seed layer slurry corroding silicon nitride and alumina is not higher than that of the base state, thereby ensuring a good contact resistance level. In addition to the glass phase and silver, the other components in the first slurry are mainly organic components that play a lubricating role, which volatilize after high-temperature sintering and drying.

[0045] Furthermore, this application optimizes the horizontal distribution of surface roughness in the first metal layer, specifically: Along the length of the gate line, the surface profile of the first metal layer includes alternating raised regions A and recessed regions B, wherein there is a height difference between the raised regions A and the recessed regions B.

[0046] This application designs the surface profile of the first metal layer to include alternating raised and recessed areas, thereby improving the overall roughness of the first metal layer and increasing its specific surface area. This reduces the interfacial resistance between the first and second metal layers and avoids the problem of poor contact at the interface between the two metal layers when two different pastes are used for step-by-step printing in the prior art. As a result, the second metal layer can ensure excellent conductivity with only a low silver content.

[0047] It should be noted that the raised area A and the recessed area B in this application are mainly distinguished by the printing height. The overall printing height (the printing height of the highest point) of the raised area A is higher than that of the recessed area. For example, in screen printing, during the grid screen printing process, the ink penetration is uneven due to the obstruction of the steel wire, which easily forms a grid structure with varying heights. That is, raised areas are printed in areas without steel wire obstruction, while recessed areas are printed in areas with steel wire obstruction.

[0048] More preferably, the horizontal distance L1 between the highest points of adjacent raised regions A is 20 to 100 micrometers, and / or the height difference h1 between the highest points of adjacent raised regions and recessed regions is 0.01 to 5 micrometers.

[0049] Wherein, the horizontal distance L1 between the highest points of adjacent raised regions A and the height difference h1 between the highest points of raised region A and recessed region B are as follows: Figure 2As indicated in the label, the horizontal spacing between the highest points of adjacent raised areas A refers to the horizontal distance between the peaks of adjacent raised areas formed by printing. This parameter can be adjusted by changing the mesh count of the screen and the arrangement of the longitudinal and transverse steel wires. The height difference h1 between the highest points of adjacent raised areas A and recessed areas B refers to the height difference between the highest point (peak) of raised area A and the highest point (peak) of recessed area B along the same scanning direction parallel to the length of the grid line. This value is directly related to the surface roughness and the effective contact area of ​​the two metal layers.

[0050] For example, the horizontal distance L1 between the highest points of adjacent raised areas can be 20 micrometers, 30 micrometers, 35 micrometers, 46 micrometers, 50 micrometers, 70 micrometers, 90 micrometers or 100 micrometers, etc.; the height difference h1 between the highest points of adjacent raised areas and recessed areas can be 0.01~1 micrometers, 0.01~2 micrometers, 1~2.5 micrometers, 2~4 micrometers, 1~4 micrometers, 1~5 micrometers, etc., preferably 1~5 micrometers, more preferably 1~4 micrometers, and even more preferably 1.3~4 micrometers.

[0051] Furthermore, for the same grid line, the horizontal distance L1 between the highest points of adjacent raised areas and the height difference h1 between the highest points of raised and recessed areas can both be fixed values ​​or within a certain range. For example, if the same grid line contains multiple different raised areas and multiple different recessed areas, the horizontal distance between different adjacent raised areas can be the same or different; similarly, the height difference between the highest points of different raised and recessed areas can be the same or different.

[0052] Furthermore, this application optimizes the horizontal distribution of surface roughness in the first metal layer, and also includes: The raised and / or recessed areas may also include sections with gently undulating heights.

[0053] Furthermore, the gently undulating height section includes alternating small protrusions and depressions along the length of the gate line; that is, this gently undulating height section also has a high-low undulation structure, but its height fluctuation is relatively small. The alternating distribution of small protrusions and depressions greatly optimizes the horizontal distribution of surface roughness of the first metal layer.

[0054] This application further optimizes the surface morphology of the first metal layer by designing the height undulation smooth section of the raised and / or recessed regions and the specific structure of the height undulation smooth section, thereby increasing the specific surface area of ​​the first metal layer and further reducing the interface resistance between the first and second metal layers. Thus, while ensuring conductivity, the silver content of the second metal layer is further reduced.

[0055] More preferably, the height range h2 of the gently undulating section is 0.01 to 3 micrometers. For example, the height range h2 of the gently undulating section can be 0.01 micrometers, 0.05 micrometers, 1.1 micrometers, 1.6 micrometers, 2.4 micrometers, or 3 micrometers, etc. Here, the height range refers to the maximum height difference between the small protruding peaks and the concave valleys of the gently undulating section.

[0056] More preferably, the horizontal distance L2 between the highest points (adjacent peaks) of adjacent small protrusions in the gently undulating section is 0.01~10 micrometers, for example, it can be 0.01 micrometers, 0.03 micrometers, 0.05 micrometers, 1.0 micrometers, 1.3 micrometers, 1.5 micrometers, 1.8 micrometers, 2 micrometers, 5 micrometers, 7 micrometers or 10 micrometers, etc.

[0057] like Figure 3 As shown, in some optional embodiments, for the same cell grid line, the raised area of ​​its first metal layer may not include a height undulation smooth section, or it may include a height undulation smooth section, or some raised areas may include a height undulation smooth section and some raised areas may not include a height undulation smooth section.

[0058] As described above, this application effectively reduces the dependence of the second metal layer paste on silver content by optimizing the surface morphology and surface roughness distribution of the first metal layer. Specifically: In this application, the second metal layer uses a second paste, which is preferably a low-silver-content paste or even a silver-free paste.

[0059] Furthermore, the silver content of the first paste is greater than that of the second paste.

[0060] More preferably, the silver content of the second slurry is less than 30%; for example, it can be 15%, 18%, 20%, 24% or 28%, etc.

[0061] More preferably, the volume resistivity of the second slurry after sintering is 3~9 μΩ·cm.

[0062] The grid structure of the present invention includes a first metal layer and a second metal layer that are overlaid or superimposed on each other. The first metal layer serves as a seed layer and uses a high-silver-content paste. The second metal layer uses a low-silver-content or silver-free paste with a silver content of less than 30%. By optimizing the surface morphology and surface roughness of the first metal layer, it is beneficial to form a larger contact interface between the upper and lower metal layers, thereby reducing the interface resistance between the first and second metal layers. This actively reduces the dependence of the second metal layer on silver content, while ensuring excellent conductivity.

[0063] Furthermore, the first metal layer and the second metal layer at least partially overlap or intersect.

[0064] It should be further explained that, based on the optimized design of the surface morphology and surface roughness distribution of the first metal layer in this application, the specific surface area is maximized and the dependence of the second metal layer on the contact area of ​​the first metal layer is reduced. That is, in this application, as long as the second metal layer and the first metal layer at least partially overlap or intersect, there are no strict requirements or restrictions on the specific distribution form and manufacturing method of the first metal layer and the second metal layer, which also greatly reduces the difficulty of the process.

[0065] Furthermore, the area of ​​the second metal layer covering the first metal layer is 20% to 100% of the total area of ​​the first metal layer. For example, it can be 20%, 30%, 40%, 50%, 60%, 70%, 80%, 100%, etc. More preferably, the area of ​​the second metal layer covering the first metal layer is 50% to 100% of the total area of ​​the first metal layer.

[0066] Specifically, such as Figure 4 As shown, the second metal layer can partially intersect the first metal layer in the horizontal direction (the two are distributed in a partially intersecting direction in the left and right direction, where the left and right direction refers to the width direction of the grid line), or the second metal layer can overprint the first metal layer, for example, the first metal layer is offset to one side inside the second metal layer, the first metal layer is symmetrically located in the central area inside the second metal layer (the width of the second metal layer extends from the edge of the first metal layer to both sides), or the second metal layer is overprinted on top of the first metal layer, but its printing width is smaller than the width of the first metal layer.

[0067] Furthermore, the second metal layer contains staggered metal particles of different sizes to achieve essentially void-free filling. This can effectively reduce the amount of silver used in the paste and the cost of the paste, while preventing adverse effects on the line resistance.

[0068] Furthermore, such as Figure 5 As shown, the second metal layer 2 contains metal particles of different sizes, including large metal particles 5 with a particle size of 0.2 to 10 micrometers and nano metal particles 4 with a particle size of 10 to 1000 nanometers.

[0069] Furthermore, the large metal particles can be pure copper, nickel, silver-coated copper, silver-coated nickel, or any combination thereof, preferably silver-coated copper, silver-coated nickel, or a combination thereof, and the nano metal can be nano silver powder, nano nickel powder, nano copper powder, or a combination thereof. For example, the large metal particles in the second slurry are silver-coated copper, and the nano metal is nano silver powder, with the surface of the silver-coated copper particles uniformly coated with silver of a thickness of 30-90 nanometers.

[0070] Furthermore, irregular pores / voids are formed within the first metal layer 1.

[0071] Combination Figure 5 As shown, in some preferred embodiments, the surface of the first metal layer 1 has pores / voids, and at least a portion of the pores / voids on the surface of the first metal layer are filled with the nano-metal 4. Since the surface of the first metal layer, i.e., the seed layer, inevitably has a loose and porous state, during the printing process of the second layer paste, the small nano-metal particles can fill some of the pores 3 on the surface of the seed layer. This helps to ensure good contact between the surface of the first metal layer 1 and the second metal layer 2, reducing the interfacial resistance between the two materials, resulting in lower line resistance, and thus more favorable for electron transport. Furthermore, by optimizing the surface profile and roughness of the first metal layer, it is even more beneficial for the nano-particles in the second metal layer to fill the pores / voids on the surface of the first metal layer, thereby further eliminating the interfacial resistance between the two metal layers and reducing the line resistance of the resulting gate lines. However, it should be noted that the pores / voids within the first metal layer are mainly formed by the volatilization of organic matter during the heating process of the slurry. Therefore, most of the pores / voids are irregular in shape, and their number and size are uncontrollable. In some optional embodiments, the length and width of the pores / voids within the first metal layer are both between 0.1 and 10 micrometers.

[0072] In the prior art, the printing dimensions in the basic state (BL state, i.e., using only high-silver-content paste to fabricate gate lines) are typically: a printing width of 25-35 micrometers and a height of 3-6 micrometers. In a further preferred embodiment of this application, with the second metal layer superimposed: the printing width of the first metal layer is 5-50 micrometers, preferably 5-35 micrometers, and the printing height is 0.5-3.5 micrometers, preferably 0.5-3 micrometers, and more preferably 1-3 micrometers; the overall printing width of the gate line after superimposing the second metal layer is 10-100 micrometers, and the printing height is 1-30 micrometers. Optimized control of the printing dimensions helps ensure that the seed layer paste with lower wet weight forms a good ohmic contact with the semiconductor substrate, ensuring that its contact resistance is not higher than that in the basic state; and the overprinting of the second metal layer can achieve a line resistance not higher than that in the basic state.

[0073] It should be noted that for the same gate line, the printing width of its first metal layer and / or second metal layer can be a fixed value or different values ​​at different positions; similarly, the printing height of the first metal layer can also be different at different positions, for example, the height of the raised area at different positions is different.

[0074] Under basic conditions, the resulting gate wire resistance is typically 1~4 Ω / cm, and the contact resistivity is typically 2.5~4.5 mΩ / cm.2 After the second metal layer is overprinted, the gate line resistance and contact resistance of this application are both no greater than those in the BL state, with a line resistance of 1~5 Ω / cm and a contact resistivity of 1~4 mΩ / cm. 2 .

[0075] This invention also provides a method for fabricating the above-mentioned gate wire structure, comprising: The first metal layer is formed on the surface of the semiconductor substrate of the solar cell by screen printing technology; A second metal layer that at least partially overlaps or intersects with the first metal layer is formed on the surface of a semiconductor substrate of a solar cell by screen printing.

[0076] This invention also provides a solar cell, including a semiconductor substrate, the surface of which is provided with the grid line structure described in this invention.

[0077] Furthermore, the gate line structure is located on the front or back side of the semiconductor substrate; and / or the gate line structure is a main gate or a sub-gate.

[0078] This invention also provides a stacked battery, comprising a top battery, an intermediate connecting layer, and a bottom battery stacked sequentially. The bottom battery is provided with the grid structure described in this invention, or uses the solar cell described in this invention.

[0079] This invention also provides a photovoltaic module, including the grid structure described in this invention, or the solar cell described in this invention, or the tandem cell described in this invention.

[0080] The present application will be further described below with reference to specific embodiments. It should be noted that the grid structure of the present application has no requirements or limitations on the type of battery, the distribution position (front or back), or the type of grid (main grid or fine grid). In the following embodiments, the technical solution of the present application is further described using the back fine grid applied to the TOPCON battery as an example. In the comparison and embodiments, the same number of grid lines of the TOPCON battery are used for parallel comparison. The front and back main grids are both 16, the front fine grid is 232 grids, and the back fine grid is 228 grids.

[0081] Example 1 This embodiment takes the TOPCON battery as an example. The silicon wafer has a size of 183.75×210 cm. There are 16 main grids on both the front and back sides, 232 fine grids on the front side and 228 fine grids on the back side. The fine grids on the back side include a first metal layer and a second metal layer. The first metal layer serves as a seed layer and is printed using a first paste with a silver content of 80%. The second metal layer is printed using a second paste with a silver content of 20%.

[0082] The preparation method of the TOPCON battery includes the following steps: S1, Printed back main grid; S2. Printing the seed layer grid on the back (i.e., the first metal layer); this seed layer grid is printed using a paste with an 80% silver content, and the printing width varies from 15 to 36 micrometers, with an average width of 20 micrometers. The printing height varies from 1 to 3.5 micrometers. After printing, irregular pores / voids are formed on the surface and inside of the seed layer grid (e.g., Figure 6 (as shown) S3, Printed front main grid; S4, Printed fine grid on the front; S5, sintering; S6, Light Injection; S7. A second metal layer grid is printed on the back side; this second metal layer grid is printed using a second paste with a silver content of 20%, and the average printed width after overprinting is 38.15 micrometers, and the average height is 9.51 micrometers. Specifically, such as... Figure 4 Overprint type 3 ( Figure 4 (as shown in d) or overprint type 4 ( Figure 4 As shown in (e), in this embodiment, the second metal layer completely covers the first metal layer.

[0083] Combination Figure 6 , Figure 7 As shown, the second metal layer obtained after printing has metal particles of different sizes stacked interlaced in the fine grid. The metal particles of different sizes include silver-coated copper metal with a particle size of 0.2 to 10 micrometers and nano-silver particles with a particle size of about 50 nanometers. After printing, the second metal layer completely covers the first metal layer (100% coverage), so that the surface areas of the first metal layer and the second metal layer are in complete contact. S8, laser-induced sintering, testing and sorting.

[0084] Combination Figures 8-19 As shown, the printing width and printing height of the first gate line are different at different positions along the length of the gate line. Along the length extension direction of the gate line, the surface contour of the first metal layer includes alternating raised and recessed areas. The horizontal distance L1 between the highest points of adjacent raised areas is about 84 to 86 micrometers, and the height difference h1 between the highest points of the raised and recessed areas is about 1.4 to 1.8 micrometers (the height difference h1 may vary for different gate lines). The recessed area includes a section with gentle height undulations, and the height difference h2 of this section is about 0.2 micrometers.

[0085] The wire resistance of the back-side fine grid prepared in this embodiment is 2.5 Ω / cm, and the contact resistivity is 2.4 mΩ·cm. 2 .

[0086] Example 2 The main difference between the TOPCON battery fabrication method in this embodiment and that in Embodiment 1 is: In this embodiment, the overprinting method of the second metal layer and the first metal layer adopts... Figure 4 As shown in (b), the overprinting type 1 has an overlap width of about 4 micrometers between the second metal layer and the first metal layer, accounting for about 20% of the surface contact area of ​​the first metal layer; the overall average printing width of the grid line after overprinting the second metal layer is 45.3 micrometers and the height is 8.7 micrometers.

[0087] The wire resistance of the back-side fine grid obtained in this embodiment is 2.65 Ω / cm, and the contact resistivity is 2.72 mΩ·cm. 2 .

[0088] Example 3 The main difference between the TOPCON battery fabrication method in this embodiment and that in Embodiment 1 is: In this embodiment, the overprinting method of the second metal layer and the first metal layer adopts... Figure 4 As shown in (c), the overprinting type 2 has an overlap width of about 10 micrometers between the second metal layer and the first metal layer, accounting for about 50% of the surface contact area of ​​the first metal layer; the overall average printing width of the grid line after overprinting the second metal layer is about 40.3 micrometers, and the height is about 9.3 micrometers.

[0089] The wire resistance of the fine back grid obtained in this embodiment is 2.55 Ω / cm, and the contact resistivity is 2.5 mΩ·cm. 2 .

[0090] Example 4 The main difference between the TOPCON battery fabrication method in this embodiment and that in Embodiment 1 is: In this embodiment, the first metal layer has a grid pattern with an alternating printing width in the range of 25 to 42 micrometers, an average width of 36 micrometers, a maximum height difference h1 between the highest point of adjacent protruding and recessed areas of about 1.3 micrometers, and a height difference h2 between the gently undulating sections of the recessed area of ​​about 0.05 micrometers. The overprinting method of the second metal layer and the first metal layer adopts Figure 4 In the overprinting type 5 shown in (f), the second metal layer is superimposed on the first metal layer, and the printing width is smaller than that of the first metal layer, accounting for 50% of the surface contact area of ​​the first metal layer; the overall height of the grid line after overprinting the second metal layer is about 11.3 micrometers.

[0091] The wire resistance of the back-side fine grid obtained in this embodiment is 2.3 Ω / cm, and the contact resistivity is 2.1 mΩ·cm. 2 .

[0092] Comparative Example 1 The preparation method of the TOPCON battery in this comparative example includes the following steps: S1. Print the main grid on the back, 16 grids in total; S2. Printed back grid; The back grid is printed with a silver content of 92%, and its printing width is 31.63 micrometers and its height is 5.35 micrometers. S3, Printed front main grid; S4, Printed fine grid on the front; S5, sintering; S6, Light Injection; S7, laser-induced sintering, testing and sorting.

[0093] The fine grid on the back side obtained in this comparative example is as follows: Figure 4 As shown in (a), which only contains the first metal layer, its line resistance is 4 Ω / cm and its contact resistivity is 2.6 mΩ·cm. 2 .

[0094] Comparative Example 2 The main difference between the TOPCON battery fabrication method in this comparative example and Example 1 is that the first metal layer in this comparative example is printed almost uniformly, without the raised and recessed areas found in this application; the line resistance of the back grid obtained in this comparative example is 2.63 Ω / cm, and the contact resistivity is 3.8 mΩ·cm. 2 .

[0095] Table 1. Parallel comparison data of cell efficiency in Examples 1-4 and Comparative Examples 1 and 2

[0096] The parallel comparison data of the efficiency of the solar cells obtained in Examples 1-4 and Comparative Examples 1 and 2 are shown in Table 1 above. As can be seen from Table 1, by adopting the double-layer overprinted / overprinted grid line structure of this application and optimizing the surface morphology and roughness of the first metal layer, not only can the amount of silver be effectively reduced, but also the interface resistance between the first metal layer and the second metal layer, as well as the line resistance of the obtained grid lines, can be effectively reduced, thus helping to further ensure the conversion efficiency of the solar cell.

Claims

1. A grid structure for a solar cell, characterized in that, It includes a first metal layer and a second metal layer, wherein: The first metal layer serves as a seed layer, and it is made from a first slurry; Along the length extension direction of the gate line, the surface profile of the first metal layer includes alternating raised and recessed regions, wherein there is a height difference between the raised and recessed regions; The second metal layer is made of a second slurry, and metal particles of different sizes are stacked alternately within the second metal layer; The silver content of the first slurry is greater than that of the second slurry, and the first metal layer and the second metal layer at least partially overlap or intersect.

2. The grid structure of the solar cell according to claim 1, characterized in that, The silver content of the first paste is 70wt% to 92wt%, and / or the silver content of the second paste is less than 30wt%.

3. The grid structure of the solar cell according to claim 2, characterized in that, The glass phase in the first slurry accounts for 0.5% to 5% of the total mass. And / or the volume resistivity of the second slurry after sintering is 3~9 μΩ·cm.

4. The grid structure of the solar cell according to claim 1, characterized in that, The horizontal distance L1 between the highest points of adjacent protruding areas is 20~100 micrometers; The height difference h1 between the highest point of adjacent raised and recessed areas is 0.01 to 5 micrometers.

5. The grid structure of the solar cell according to claim 1, characterized in that, The raised and / or recessed areas include sections with gently undulating heights.

6. The grid structure of the solar cell according to claim 5, characterized in that, The gently undulating section includes small protrusions and depressions that are alternately distributed along the length of the grid line.

7. The grid structure of the solar cell according to claim 6, characterized in that, The height range h2 of the gently undulating section is 0.01~3 micrometers.

8. The grid structure of the solar cell according to claim 6, characterized in that, The horizontal distance L2 between the highest points of adjacent small protrusions in the gently undulating section is 0.01~10 micrometers.

9. The grid structure of the solar cell according to any one of claims 1-8, characterized in that, The area of ​​the second metal layer covering the first metal layer is 20% to 100% of the total area of ​​the first metal layer.

10. The grid structure of the solar cell according to claim 9, characterized in that, The first metal layer has a printing width of 5 to 50 micrometers and a printing height of 0.5 to 3.5 micrometers; the printing width after stacking the second metal layer is 10 to 100 micrometers and the printing height is 1 to 30 micrometers.

11. The grid structure of the solar cell according to any one of claims 1-8, characterized in that, Irregular pores are formed within the first metal layer.

12. The grid structure of the solar cell according to claim 11, characterized in that, The length and width of the pores are both between 0.1 and 10 micrometers.

13. The grid structure of the solar cell according to any one of claims 1-8, characterized in that, The second metal layer contains metal particles of different sizes, including large metal particles with a particle size of 0.2 to 10 micrometers and nano metal particles with a particle size of 10 to 1000 nanometers.

14. The grid structure of the solar cell according to claim 13, characterized in that, The large metal particles are made of pure copper, nickel, silver-coated copper, silver-coated nickel, or any combination thereof; the nano metals are made of nano silver powder, nano nickel powder, nano copper powder, or any combination thereof.

15. The grid structure of the solar cell according to claim 13, characterized in that, The surface of the first metal layer has pores, and at least a portion of the pores on the surface of the first metal layer are filled with the nano-metal.

16. A method for fabricating a gate wire structure as described in any one of claims 1-15, characterized in that, include: The first metal layer is formed on the surface of the semiconductor substrate of the solar cell by screen printing technology; A second metal layer is formed on the surface of a semiconductor substrate of a solar cell by screen printing, which at least partially overlaps or intersects with the first metal layer.

17. A solar cell, comprising a semiconductor substrate, characterized in that, The surface of the semiconductor substrate is provided with a gate line structure as described in any one of claims 1-15.

18. The solar cell according to claim 17, characterized in that, The gate line structure is located on the front or back side of the semiconductor substrate; and / or the gate line structure is a main gate or a sub-gate.

19. A stacked battery, comprising a top battery, an intermediate connecting layer, and a bottom battery stacked sequentially, characterized in that, The bottom cell has a grid structure as described in any one of claims 1-15, or uses a solar cell as described in claim 17 or 18.

20. A photovoltaic module, characterized in that, It includes the grid structure of any one of claims 1-15, or the solar cell of claim 17 or 18, or the tandem cell of claim 19.

Citation Information

Patent Citations

  • Micro light emitting diode chip transfer method and temporary substrate

    CN118888649A

  • Photovoltaic cell and manufacturing method thereof, laminated cell and photovoltaic module

    CN121463573A

  • Solar cell and preparation method thereof

    CN121665738A